PENINGKATAN SUSTAINABILITAS RANTAI NILAI BUDIDAYA LEBAH KLANCENG KELOMPOK MALANG JAYA - Herwiyanti, Eliada; Yuniaty, Alice; Wahyu Pribadi, Fajar (LPPM ITB AAS Indonesia Surakarta, 2025)
The community service program aims to improve the sustainability of the Trigona spp. cultivation value chain. The target group is the Malang Jaya Trigona spp. cultivation group, located in Pageraji Village, Cilongok, Banyumas. Established in February 2024, the Malang Jaya group faced challenges in production, organizational management, and marketing. Efforts to address these challenges included providing appropriate technology and innovation, providing outreach and training on organizational management, and marketing. The technology and innovation assistance provided included raw materials, components, and appropriate technology tools. All of the technological and innovation assistance has been handed over on July 26, 2025. Until the time this article was written, meaning approximately 50 days have passed, the Malang Jaya group has carried out the Trigona spp. cultivation process, planting longan and santos lemon tree seedlings, better product storage and packaging practices, as well as more orderly financial and administrative recording practices by using all the technology and innovation funded by the Grant of the Directorate of Research and Community Service, Directorate General of Research and Development, Ministry of Higher Education, Science, and Technology. Thus, slowly but surely, the Malang Jaya group will experience an increase in the sustainability of the Trigona spp. cultivation value chain.